Sharing R&D Investments in Breakthrough Technologies to Control Climate Change - Santiago J. Rubio (Fondazione Eni Enrico Mattei (FEEM), 2016)
This paper examines international cooperation on technological development as an alternative to international cooperation on GHG emission reductions. In order to analyze the scope of cooperation, a three-stage technology agreement formation game is solved. First, countries decide whether or not to sign up to the agreement. Then, in the second stage, the signatories (playing together) and the non-signatories (playing individually) select their investment in R&D. In this stage, it is assumed that the signatories not only coordinate their levels of R&D investment but also pool their R&D efforts to fully internalize the spillovers of their investment in innovation. Finally, in the third stage, each country decides non-cooperatively upon its level of energy production. Emissions depend on the decisions made regarding investment and production. If a country decides to develop a breakthrough technology in the second stage, its emissions will be zero in the third stage. For linear environmental damages and quadratic investment costs, the grand coalition is stable if marginal damages are large enough to justify the development of a breakthrough technology that eliminates emissions completely, and if technology spillovers are not very important.
Keywords: D74; F53; H41; Q54; Q55; 330; International Environmental Agreements; R&D Investment; Technology Spillovers; Breakthrough Technologies